Influence of wheat varietal mixtures on yield stability, grain quality and flour rheological properties. - Zoghali, Mousa (Jihočeská univerzita, 2021)
This thesis focuses on the influence of wheat varietal mixtures on yield stability, grain quality and flour rheological properties. The aim of this study was to improve wheat yields and includes further mixing of wheat varieties through crossing, interspecific and intergeneric hybridization, biotechnology techniques, wheat mixtures. The growth of wheat mixtures will lead to yield stability, then it will lead to baking quality stability, and the rheological properties of flour will be positively influenced by the growing wheat in mixtures.
Influence of wheat varietal mixtures on yield stability, grain quality and flour rheological properties.
Keywords: Keywords: Baking quality; Protein content; Tillering capacity; Wheat varieties.; Keywords: Baking quality; Protein content; Tillering capacity; Wheat varieties.